2022
DOI: 10.1111/cobi.13982
|View full text |Cite
|
Sign up to set email alerts
|

Ecological relevance of non‐perennial rivers for the conservation of terrestrial and aquatic communities

Abstract: River conservation efforts traditionally focus on perennial watercourses (i.e., those that do not dry) and their associated aquatic biodiversity. However, most of the global river network is not perennial and thus supports both aquatic and terrestrial biodiversity. We assessed the conservation value of nonperennial rivers and streams (NPRS) in one of Europe's driest regions based on aquatic (macroinvertebrates, diatoms) and terrestrial (riparian plants, birds, and carabid beetles) community data. We mapped the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…Given the high rate of taxa turnover in our dataset, with most taxa restricted to a few sites, high representation targets could only be achieved for all taxa at the same time by selecting almost all sites simultaneously. To address this problem, a bootstrap analysis was conducted (Bruno et al, 2022), by attempting to achieve the targets for a given proportion of all taxa each time. For this, 1,000 random samples were selected containing 50% of the taxa from the total pool and identified the minimum set of locations to cover the representation targets explained above.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the high rate of taxa turnover in our dataset, with most taxa restricted to a few sites, high representation targets could only be achieved for all taxa at the same time by selecting almost all sites simultaneously. To address this problem, a bootstrap analysis was conducted (Bruno et al, 2022), by attempting to achieve the targets for a given proportion of all taxa each time. For this, 1,000 random samples were selected containing 50% of the taxa from the total pool and identified the minimum set of locations to cover the representation targets explained above.…”
Section: Methodsmentioning
confidence: 99%
“…For this, 1,000 random samples were selected containing 50% of the taxa from the total pool and identified the minimum set of locations to cover the representation targets explained above. This decision was based on the work of Bruno et al (2022), who tested three different thresholds (50%, 75%, 90%) and found that the results were consistent across the different bootstrap thresholds used. Given the lack of estimates of conservation costs across the study area, a constant cost across all locations were used (e.g., Hermoso et al, 2021) and no connectivity penalty measure was included, similar to Bruno et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations